Pengaruh Model Pembelajaran Reciprocal Teaching terhadap Hasil Belajar Matematika dengan Mengontrol Kemandirian Belajar (FPMIPA IKIP PGRI Bali, 2020)
The aim of this study is to anaysis of the effect of reciprocal teaching learning model on mathematics learning outcome by controlling learning independence. The type of this research is quasi experiment and using Non Equivalent Control Group Design. The populations are the grade VII students of SMP Negeri 3 Mengwi on 2019/2020 academic years, which consist of 11 classes with 339 numbers of students. Sample selection using random sampling technique, so that the class VII-F (30 students) as the experimental class and the class VII-E (30 students) as the control class. The data of learning independence were collected using a questionnaire, while the mathematics learning outcome data were collected using a learning achievement test. The data was analysed by using t-test and one way analysis of covarian (Ancova). The results of data analysis indicate that: (1) there are differences in the mathematics learning outcomes of students who take reciprocal teaching learning models and students who take conventional learning; (2) there are differences in mathematics learning outcomes between students who take reciprocal teaching learning models and students who take conventional learning after controlling for learning independence.